SCREENING OF CHICKPEA CULTIVARS AGAINST WILT AND ROOT ROT COMPLEX DISEASE OF CHICKPEA - RAJKUMARI PADAMINI; KUSUM MATHUR; AMIT TRIVEDI (The Bioscan, 2020)
Ten chickpea cultivars were screened to find out the source of resistance against F. solani, Fusarium oxysporum f. sp. ciceri (Foc) and R. solani causing wilt and root rot complex of chickpea. The experiment was conducted during rabi (2012-13) and (2013-14) using the varieties Dahod Yellow, Pratap Chana -1, Avrodhi, RSG-888, RAJ- 1581, BGD-72, BG-391, BG-1053, GMG-469 and P- 1080 under soil inoculation activity growing virulent cultures of F. solani (isolate SRH Fs-5), Foc (isolate BNS Foc-1) and R. solani (isolate BNS Rs-6). Pooled data revealed among the varieties, the lowest germination (61.0 %) was recorded with Dahod Yellow, followed by variety BG-391 with 62.8 % germination. BGD-72 showed 68.5 % germination, BG-1053 showed 70.0 % germination, Pratap Chana-1 showed 72.5 % germination, P-1080 showed 73.5 % germination, RAJ-1581 showed 75.6 % germination and 78.0 % germination with GNG-469. The highest germination 82.5 % was recorded with Avrodhi. The result showed Avrodhi to be highly resistant to wilt and root rot complex of chickpea. Varieties GNG-469, RAJ-1581, P-1080 and Pratap Chana-1 were moderately resistant, while BG- 1053, BGD-72, BG-391 and RSG-888 were moderately susceptible. The popular cultivar Dahod Yellow was highly susceptible.